Ectopic Prostatic Tissue in the Right Paracolic Gutter: A Case Report - Ahn, Bokung; Lee, Youngseok; Sim, Ki Choon; Lee, Jeong Hyeon (Urology Journal, 2020)
Ectopic prostatic tissue (EPT) is fairly uncommon; however, when reported, it is most often found in the male genitourinary tract. Since extragenitourinary EPT is very rare, it is extremely difficult to properly diagnose preoperatively.(1-3) This article describes a unique case of EPT found in the right paracolic gutter.